2017
DOI: 10.5194/hess-21-5089-2017
|View full text |Cite
|
Sign up to set email alerts
|

Using isotopes to constrain water flux and age estimates in snow-influenced catchments using the STARR (Spatially distributed Tracer-Aided Rainfall–Runoff) model

Abstract: Abstract. Tracer-aided hydrological models are increasingly used to reveal fundamentals of runoff generation processes and water travel times in catchments. Modelling studies integrating stable water isotopes as tracers are mostly based in temperate and warm climates, leaving catchments with strong snow influences underrepresented in the literature. Such catchments are challenging, as the isotopic tracer signals in water entering the catchments as snowmelt are typically distorted from incoming precipitation du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
91
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 87 publications
8
91
1
Order By: Relevance
“…Catchment runoff ages and plot scale AR show also similar dynamics at Dorset, as Piovano et al (in review) also reported generally increasing water ages in the runoff during the snow dominated winter, while runoff ages during summer were more dependent on the rainfall pattern. We see also similarities at Krycklan with increasing water ages for catchment runoff 15 (Ala-aho et al, 2017b) and soil water recharge throughout the snow dominated winter. However, while snowmelt leads to a rapid decrease in water ages at both the catchment and the plot scales, the cessation of the soil recharge flux in the summer in the 1D-simulations results in the largest AR during fall when older soil water becomes remobilized.…”
Section: 3mentioning
confidence: 54%
See 4 more Smart Citations
“…Catchment runoff ages and plot scale AR show also similar dynamics at Dorset, as Piovano et al (in review) also reported generally increasing water ages in the runoff during the snow dominated winter, while runoff ages during summer were more dependent on the rainfall pattern. We see also similarities at Krycklan with increasing water ages for catchment runoff 15 (Ala-aho et al, 2017b) and soil water recharge throughout the snow dominated winter. However, while snowmelt leads to a rapid decrease in water ages at both the catchment and the plot scales, the cessation of the soil recharge flux in the summer in the 1D-simulations results in the largest AR during fall when older soil water becomes remobilized.…”
Section: 3mentioning
confidence: 54%
“…The R water ages at 50 cm depth in this study are obviously younger than catchment scale runoff water ages Ala-aho et al, 2017b;Benettin et al, 2017;Kuppel et al, 2018). Nevertheless, there are similarities regarding the age dynamics.…”
Section: 3mentioning
confidence: 55%
See 3 more Smart Citations